2022
DOI: 10.1007/s11109-022-09773-7
|View full text |Cite
|
Sign up to set email alerts
|

Valuing Politics: Explaining Citizen’s Normative Conceptions of Citizenship

Abstract: Civic duty is a critical feature of explanations of political participation, but why do individuals differ in their propensity to adopt particular civic duty norms? We argue that norms are likely to be adopted when congruent with underlying values and support this contention using evidence from the European Social Survey. We show that individuals who prioritize self-transcendence values (which capture altruistic goals) place much greater emphasis on norms positively related to participation while individuals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…In line with previous studies (Gagrčin & Porten-Cheé, 2023;Kunst et al, 2021;Ziegele et al, 2020), this vocabulary foregrounds solidarity and altruism, which enables people to transcend immediate personal matters when thinking about intervention and instead focus on more distant goals (Fowler & Kam, 2003;Robison, 2022). Accordingly, the aspirational vocabulary disapproves of non-intervention in general and people who do not intervene in particular.…”
Section: A Typology Of Users' Justifications Related To Intervention ...supporting
confidence: 75%
“…In line with previous studies (Gagrčin & Porten-Cheé, 2023;Kunst et al, 2021;Ziegele et al, 2020), this vocabulary foregrounds solidarity and altruism, which enables people to transcend immediate personal matters when thinking about intervention and instead focus on more distant goals (Fowler & Kam, 2003;Robison, 2022). Accordingly, the aspirational vocabulary disapproves of non-intervention in general and people who do not intervene in particular.…”
Section: A Typology Of Users' Justifications Related To Intervention ...supporting
confidence: 75%
“…It has been supported in the previous literature that individuals might differ in their propensity to show their responsibility and duty toward society, and these variations appear due to their personal values. Thus, the adoption of a particular societally responsible action appears when the same is consistent with individuals’ perceived values (Robison 2022).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…It has, likewise, been applied in explaining social phenomena, such as mobility and brain drain intentions (Petreska, Prodanova, and Kocarev 2023). Moreover, perceived values have been a proven antecedent of citizens’ political choices (Wang 2016; Robison 2022). The social and political environment has been especially emphasized in the justification of the citizens’ civic duty and related experiences (Hansen and Tyner 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“… Parker and Axtell (2001) proposed the perspective taking theory and suggested that the effect of taking the perspective of other people would change an employee’s original traits and dispositions, and the magnitude of the change depends upon the person’s motivation ( Škerlavaj et al, 2018 ). Within an individual’s scope of work, the social motivation of volunteering directly benefits other people while improving one’s work performance and the drive to succeed, and therefore, it is OCB-related ( Robison, 2022 ). Moreover, people with perspective taking can put themselves in others’ position to understand and feel the thoughts and ideas of others, so as to form a motivation to help others and promote them to show more altruistic behaviors, such as OCB ( Sabati, 2022 ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%